Elasticity of demand for petrol in Ireland - comment - Arthur, W. Brian (Economic & Social Studies, 1973)
In an article in this journal (April 1972) W . K. O'Riordan estimated the price elasticity of petrol to be between minus 1.2 and minus 1.7. These values are surprisingly high. Petrol is expensive but the other major expenses in running a car, insurance, depreciation, road taxes, and maintenance, account for the greater part of the car owner's annual bill, perhaps as much as 75 per cent. W i th such a heavy annual investment in the privilege of driving, the motorist can hardly be expected to cut down his mileage significantly because of a petrol price increase. Petrol, we would suspect, is unlikely to be very price-elastic.
Keywords: Petrol Demand; Ireland